Teaching Professionals Knowledge of New Techno Pedagogical Approach Stop Motion Studio for Slow Learners - Jagadeesh, K.; Subramanian, A. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Background: A ―Slow Learners‖ is not a diagnosing category, it is a term people use to describe a student who has the ability to learn necessary academic skills, but at rate and depth below average same age peers. In order to grasp new concepts, a slow learners needs more time, more repetition, and often more resources from teachers to be successful. The research study focused on Teaching Professionals‘ Knowledge of New Techno Pedagogical Approach Stop Motion Studio for Slow Learners. Method: This study was conducted in various districts of Tamil Nadu. Survey method through survey monkey was employed to collect the data through questionnaire (open-ended) by adopting Judgment or Purposive sampling Technique. Sample: The sample size of this study comprises 118 teaching professionals working and studying various schools and colleges in Tamil Nadu. The responses from the questionnaire have been complied in percentages. Objective: The objective of the study is to analyze the teaching professionals Knowledge of new techno pedagogical approach Stop Motion Studio for slow learners. Result: The findings provide a variety of information that was based on objective of the study.